Self-standing polymer-functionalized reduced graphene oxide papers obtained via a UV-process. Issue 116 (6th November 2015) - Roppolo, I.; Chiappone, A.; Boggione, L.; Castellino, M.; Bejtka, K.; Pirri, C. F.; Sangermano, M.; Chiolerio, A.
Abstract : The mechanical and electrical properties of novel polymer-grafted RGO papers, synthesized via a two-step UV-induced method, were studied. Abstract : Graphene based materials are attracting great attention every day due to their outstanding properties. Widening their potentialities through synergic effects in conjunction with other materials represents an intriguing challenge in order to obtain lighter and multi-functional composites. In this paper, novel self-standing graphene-based paper-like sheets are investigated, obtained via a facile dual step UV-induced process. This method, employing graphene oxide as a starting material, allows the obtaining of polymeric functionalized reduced graphene oxide papers that could be easily handled, featuring improved mechanical and peculiar electrical properties. The mechanical and thermal properties were investigated as well as their electrical response under different stimuli, such as temperature and humidity, showing remarkable changes.